Evening chronotype, disordered eating behavior, and poor dietary habits in bipolar disorder. (30th May 2020) - Romo‐Nava, F.; Blom, T. J.; Guerdjikova, A.; Winham, S. J.; Cuellar‐Barboza, A. B.; Nunez, N. A.; Singh, B.; Biernacka, J. M.; Frye, M. A.; McElroy, S. L.
Abstract : Objective: Our aim was to evaluate the relationship between evening chronotype, a proxy marker of circadian system dysfunction, and disordered eating behavior and poor dietary habits in individuals with bipolar disorder (BD). Methods: In this cross‐sectional study, we evaluated 783 adults with BD. Chronotype was determined using item 5 from the reduced Morningness‐Eveningness Questionnaire. The Eating Disorder Diagnostic Scale (EDDS) and the Rapid Eating Assessment for Participants—Shortened Version (REAP‐S) were used to assess disordered eating behavior and dietary habits respectively. General linear models and logistic regression models were utilized to evaluate differences between chronotype groups. Results: Two hundred and eight (27%) BD participants self‐identified as having evening chronotypes. Compared to non‐evening types, evening types were younger ( P < 0.01) and, after controlling for age, had higher mean EDDS composite z‐scores ( P < 0.01); higher rates of binge‐eating (BE) behavior ( P = 0.04), bulimia nervosa ( P < 0.01), and nocturnal eating binges ( P < 0.01); and a higher body mass index ( P = 0.04). Compared to non‐evening types, evening chronotypes had a lower REAP‐S overall score ( P < 0.01) and scored lower on the 'healthy foods' and 'avoidance of unhealthy food' factors. Evening types also skipped breakfast more often ( P < 0.01), ate less fruit ( P = 0.02) and vegetables ( P = 0.04), and consumed more fried foods ( P < 0.01), unhealthy snacks ( P = 0.02), and soft drinks ( P = 0.01). Conclusions: Our findings suggest that the circadian system plays a role in the disordered eating and unhealthy dietary behaviors observed in BD patients. The circadian system may therefore represent a therapeutic target in BD‐associated morbidity that warrants further investigation.